An intersection property gluing on weak outwardly hyperconvex spaces. (2020) - Aftab Kabir, Qazi; Bhardwaj, Ramakant; Mohammad, Masroor; Verma, Rupali; Kumar Brave, Sharad
Abstract: In this paper we have generalizeda certain and adequate circumstance nether which gluings of H- metric spaces on weak outwardly hyperconvex subsets are hyperconvex. Our results are the extension of the results obtained by B. Miesch and M. Pavon (J. Topo. Anal., volume 9, issue 3, September 2017), to the case of intersection property for gluing on weak outwardly hyperconvex subsets gives rise to H- spaces